2020
DOI: 10.1002/agj2.20063
|View full text |Cite
|
Sign up to set email alerts
|

Midseason application of organic fertilizer improves yield and nitrogen uptake in rice

Abstract: Organic rice (Oryza sativa L.) systems in California utilize a 30‐d drain approximately one month into the growing season to control weeds. This drain may result in N losses and reduce yields. Two field trials were initiated to evaluate whether top‐dressing fertilizer N following the drain period could mitigate this problem by increasing N uptake and yields. Treatments evaluated rates and sources of commercially available organic fertilizers varying in N content and C to N ratio. The six treatments were a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In contrast, our results showed that the RNF and CRF treatments exhibited no significant differences in NUE under the same N level, which may be attributable Hu et al 10.3389/fpls.2023.1281309 to the different release times of CRU or the CRU-CU mixing ratio. In previous studies, under reduced N conditions, increasing plant density or organic fertilizer increased N uptake and NUE (Murray and Linquist, 2020;Luo et al, 2022). In this study, the CRF+ID treatment improved N uptake and NUE (NRE, NAE, and FPN) compared with RNF and CRF treatments.…”
Section: Effects Of Reduced N and Simplified N Fertilizer Application...mentioning
confidence: 85%
“…In contrast, our results showed that the RNF and CRF treatments exhibited no significant differences in NUE under the same N level, which may be attributable Hu et al 10.3389/fpls.2023.1281309 to the different release times of CRU or the CRU-CU mixing ratio. In previous studies, under reduced N conditions, increasing plant density or organic fertilizer increased N uptake and NUE (Murray and Linquist, 2020;Luo et al, 2022). In this study, the CRF+ID treatment improved N uptake and NUE (NRE, NAE, and FPN) compared with RNF and CRF treatments.…”
Section: Effects Of Reduced N and Simplified N Fertilizer Application...mentioning
confidence: 85%
“…Fields are then reflooded and remain so for duration of the season. Fertility management in these systems often involves the application of manures before planting and just before reflooding, following the weed control DD (Murray et al., 2020; Wild et al., 2011).…”
Section: Introductionmentioning
confidence: 99%